Promoting Islamic Philanthropy as a Social Finance Instrument in Economic Development in Indonesia - Vina Fithriana Wibisono; Suyoto Arief; Syamsuri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Indonesia's economic development from year to year has always been characterized by primary problems, namely poverty and unemployment, which are caused by unequal distribution of economic results to those in need and are dominated by capitalist economic principles. In overcoming these problems, Islamic socio-economic pillars are present that can support people's lives, namely the pillars of Islamic philanthropy. This research aims to explain the theory and practice of Islamic philanthropy in Indonesia as a form of contribution or solution in solving several economic problems or for the benefit of society. This type of research is a literature study by collecting data through several pieces of literature or documentation. The results of this research show that Islamic philanthropy is classified into two things, namely as social services and social change, which have the impact of being a more productive and efficient solution for economic development in Indonesia.